2016
DOI: 10.1093/pm/pnw180
|View full text |Cite
|
Sign up to set email alerts
|

HIV Distal Neuropathic Pain Is Associated with Smaller Ventral Posterior Cingulate Cortex

Abstract: Objective. Despite modern antiretroviral therapy, HIV-associated neuropathy is one of the most prevalent, disabling and treatment-resistant complications of HIV disease. The presence and intensity of distal neuropathic pain is not fully explained by the degree of peripheral nerve damage. A better understanding of brain structure in HIV distal neuropathic pain may help explain why some patients with HIV neuropathy report pain while the majority does not. Previously, we reported that more intense distal neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 92 publications
2
14
0
Order By: Relevance
“…Bilateral reduction in regional cerebral blood flow has been documented in the cingulofrontal transitional cortex and posterior cingulate cortex during noxious stimulation of the left hand 35 . Similar to our results, in patients with HIV-associated distal neuropathic pain, changes (increase) were restricted to the left posterior cingulate cortex 36 . A negative correlation between pain thresholds and cortical thickness was also reported on the left 22 .…”
Section: Discussionsupporting
confidence: 91%
“…Bilateral reduction in regional cerebral blood flow has been documented in the cingulofrontal transitional cortex and posterior cingulate cortex during noxious stimulation of the left hand 35 . Similar to our results, in patients with HIV-associated distal neuropathic pain, changes (increase) were restricted to the left posterior cingulate cortex 36 . A negative correlation between pain thresholds and cortical thickness was also reported on the left 22 .…”
Section: Discussionsupporting
confidence: 91%
“…Brain regions that correlated with perception of vibration included frontal precentral, frontal medial, and temporal superior cortices; the cingulate mid-posterior cortex, implicated in pain perception, and previously reported as relevant to both diabetic and HIV-related neuropathies (Sugimine et al, 2016, Hsieh et al, 2015, Keltner et al, 2017); the thalamus, relevant to perception of pain (Geha and Apkarian, 2005, Peyron et al, 2000), and sometimes directly implicated in neuropathy (Selvarajah et al, 2011); and the pons, which has been reported in case studies of rare neuropathies (cf., Weinmann, 1967, Rossi et al., 1986). Consistent with posterior cingulate involvement, our recent study in HIV found relations between subjective symptoms of neuropathy and smaller parietal precuneus volume (Zahr et al, 2019); both regions support introspection and self-awareness (Kjaer et al, 2002, Jacob and Kostev, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Recent evidence supports Central Nervous System (CNS) involvement in peripheral neuropathy (e.g., Tesfaye et al, 2016, Zahr et al, 2019, Keltner et al, 2017, Pfefferbaum et al, 2009). Diabetes with neuropathy relative to diabetes without neuropathy is associated with compromise in volume of cingulate cortex (Boland et al, 2014), implicated in the affective processing of pain (Coppieters et al, 2017, Buckalew et al., 2008, Absinta et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to CIPN, HIV patients often present with neuropathy and neuropathic pain (Ellis et al, 2010; Wiebe et al, 2011), but here, nerve injury can be due to the infection itself or result from treatment-induced toxicity (Kranick and Nath, 2012). In HIV, changes in CNS structure (Chiang et al, 2007; Jahanshad et al, 2012; Keltner et al, 2014; Thompson et al, 2005; Thompson and Jahanshad, 2015), for instance, those occurring in posterior cingulate cortex, may contribute to the spectrum of symptoms reported by HIV patients and also objectively distinguish painful vs. painless HIV neuropathy (Keltner et al, 2016).…”
Section: Neuropathic Pain (Np)mentioning
confidence: 99%